The Effect of Using a Spinal Orthosis on Non-Specific Lower Back Pain: Literature review - Suprayogi, Dody; Zubaidi, Alfan; Rahayu, Listianingrum Budi (Poltekkes Kemenkes Jakarta I, 2025)
Background: Over time, various problems have emerged alongside societal developments, including those in the health sector. One common issue is musculoskeletal disorders, particularly low back pain (LBP). Nonspecific Low Back Pain (NSLBP) refers to a pain syndrome in the lower back region without a clearly identifiable cause. Spinal orthosis has been proposed as a potential treatment for back pain. Aims: This study aims to examine the effectiveness of spinal orthosis in managing low back pain through a literature review. Methods and Subjects: A literature review was conducted using databases such as Google Scholar, PubMed, and ScienceDirect. The keywords used included